PENERAPAN MODEL PEMBELAJARAN ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION DALAM MENINGKATKAN HASIL BELAJAR TRIGONOMETRI - Isran, Isran; Wibowo, Edy; Laruli, Lakilo (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
The problem faced by students is the achievement of mathematics learning outcomes, particularly in trigonometry; therefore, an innovative learning model is needed to improve trigonometry learning outcomes. One innovative learning model is the Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) model. This study aims to determine the effectiveness of the Assurance, Relevance, Interest, Assessment, Satisfaction learning model on trigonometry learning outcomes in grade X at SMKS Kristen Padang Sappa. The research employed a pre-experimental study design with a one-group pretest-posttest design. The population in this study consisted of all students at SMKS Kristen Padang Sappa. The sample comprised 21 male and female students in grade X at SMKS Kristen Padang Sappa. The Assurance, Relevance, Interest, Assessment, Satisfaction learning model was implemented over two sessions with trigonometry material instruction. Evaluation was conducted by examining trigonometry learning outcomes. The instrument used was an achievement test consisting of 10 essay questions. Validity testing results indicated that all 10 items were valid, with a Cronbach's alpha coefficient of 0.86, indicating high reliability. The data analysis technique employed a paired sample t-test. The findings regarding trigonometry learning outcomes showed hypothesis test results with a significance value of 0.000. Thus, there is effectiveness of the Assurance, Relevance, Interest, Assessment, Satisfaction learning model on trigonometry learning outcomes in grade X at SMKS Kristen Padang Sappa. ABSTRAKMasalah yang dihadapi oleh siswa adalah pencapaian hasil belajar matematika diantaranya trigonometri, maka dibutuhkan model pembelajaran yang inovatif untuk meningkatkan hasil pembelajaran trigonometri. Salah satu model pembelajaran yang inovativ adalah model pembelajaran assurance, relevance, interest, assessment, satisfaction. Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran assurance, relevance, interest, assessment, satisfaction terhadap hasil belajar trigonometri di kelas X SMKS Kristen Padang Sappa. Penelitian menggunakan jenis penelitian Pre Experimen study dengan desain penelitian one group pre test and post test design. Pupulasi dalam penelitian ini adalah seluruh peserta didik di SMKS Kristen Padang Sappa. Sampel dalam penelitian ini adalah  siswa dan siswi  di kelas  X  SMKS Kristen Padang Sappa yang berjumlah 21 orang. Pemberian model pembelajaran assurance, relevance, interest, assessment, satisfaction selama dua kali pertemuan dengan pemberian materi trigonometri. Evaluasi dilakukan dengan melihat hasil belajar trigonometri. Instrumen yang digunakan adalah tes hasil belajar yang terdiri dari 10 butir soal essay. Hasil uji validitas yang dilakukan menunjukan 10 item pertanyaan dinyatakan valid, dengan koefisien alpha sebesar 0,86 artinya reliabilitasnya tinggi. Teknik analisis datanya menggunakan uji statistik paired sample t test. Dari hasil temuan  hasil belajar trigonometri diperoleh hasil uji hipotesis dengan nilai signifikansi sebesar 0,000. Dengan demikian terdapat Efektivitas model pembelajaran assurance, relevance, interest, assessment, satisfaction terhadap hasil belajar trigonometri di kelas X SMKS Kristen Padang Sappa.